Transparency in Europe: A Quantitative Study. Issue 7 (1st May 2015) - Bouder, Frederic; Way, Dominic; Löfstedt, Ragnar; Evensen, Darrick
Abstract : In recent years, European pharmaceutical regulators have increasingly committed to heightening access to raw safety‐related data as part of a wave of transparency initiatives (e.g., providing public Internet‐mediated access to clinical trials data). Yet, the regulators—who are under significant pressure—have not yet benefited from a systematic review of this new policy. In seeking to inject much needed evidence, this article explores the effects of new transparency policies designed to promote meaningful communication of risks and benefits to patients. Results of a cross‐national European survey with respondents from Great Britain, the Netherlands, Spain, France, Germany, and Sweden ( N = 5, 648) shed light on how patients and the public are likely to react to the regulators' new transparency policies. The findings demonstrate clear national variations in how European citizens are likely to react and emphasize the need to develop evidence‐based, reasoned transparency policies that integrate benefit‐risk communication. The authors conclude by providing six specific recommendations, informed by the study, that seek to improve the European transparency model both within the medical field and across health, safety, and environmental policy domains.